2020
DOI: 10.1177/2010105820979006
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of flavonoids: An experimental study on natural-killer-cell-mediated cytotoxicity against lung cancer and cytotoxic granule secretion profile

Abstract: Background: A new approach involving immune-cell-mediated cancer therapy has been adopted extensively for the sake of lung cancer treatments by utilizing natural killer (NK) cells. NK cell activity can be enhanced with certain agents, and among them are flavonoids. Thus, this study was conducted to investigate the immunomodulatory roles of apigenin, luteolin and quercetin on NK cell activity against lung cancer cells and on the secretions of perforin and granulysin profile. Methods: The NK-92 cells were grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It can block IL-6 secretion, affects immunity and inflammation by targeting many signaling pathways, and work on leukocytes. In another study from in vitro treatment, quercetin activated T cells, NK cells, and blocked IL-12 [64]. Hence, this research will show T cell proliferation and Th1 differentiation.…”
Section: Genisteinmentioning
confidence: 68%
“…It can block IL-6 secretion, affects immunity and inflammation by targeting many signaling pathways, and work on leukocytes. In another study from in vitro treatment, quercetin activated T cells, NK cells, and blocked IL-12 [64]. Hence, this research will show T cell proliferation and Th1 differentiation.…”
Section: Genisteinmentioning
confidence: 68%
“…The immunomodulatory actions of flavonoids and other constituents in honey are well known, and the use of honey as an adjuvant in cancer therapy has been recommended [ 206 ]. The effects of three flavonoids, namely apigenin, luteolin, and quercetin, on NK cell activity against lung cancer cells, and on the secretions of the cytotoxic granules perforin and granulysin were also examined [ 207 ]. Naringenin, a flavonoid product, is known to modulate mouse J774 macrophages upon infection with C. trachomatis , through modulation of TLR2, TLR4, and CD86 receptors and down-streaming of the MAPK (p38) pathway [ 208 ].…”
Section: Immune System Immunity and Cancer Immunotherapy: The Flavono...mentioning
confidence: 99%
“…The quantity and location of free hydroxyl (-OH) groups affect the efficacy of flavonoids, the secondary metabolites with immunomodulatory characteristics. [27] The methanol extract of C. sativum L. had a TFC of 60.87 mg QE/g dry weight, whereas the methanolic extract of M. koenigii had a TFC of 9.75 mg QE/g dry weight, according to D.T. Abeysinghe et al [28] and Hasna Bouhenni et al [29] The flavonoid concentration of leafy vegetables was shown to be considerably influenced by biological, environmental, genetic, seasonal, and yearly fluctuations, according to publications in the literature.…”
Section: Total Flavonoid Content Determination (Tfc)mentioning
confidence: 99%